Retelling trickster in Naapi's language - Howe, Nimachia (University Press of Colorado, 2019)
"An examination of Niitsitapisinii (Blackfoot) origin stories about one of the powerful and unpredictable creators in Niitsitapii consciousness: Naapi. Through in-depth linguistic analysis, Howe reinterprets the earliest references to Naapi, offering an authentic understanding of his identity and the meanings and functions of the stories he appears"--Provided by publisher.
Keywords: Naapi : (Trickster); Siksika Indians : Folklore; Indians of North America : Folklore; Siksika language; mustajalat; kertomusperinne; kansantarinat; myytit; tricksterit; intiaanikulttuurit; Amerikan alkuperäiskielet; maailmankuva; svartfotsindianer; berättartradition; myter; folksägner; tricksters; indiankulturer; amerikanska ursprungsspråk; världsbild